2013
DOI: 10.1128/jvi.02306-12
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz Enhances HIV-1 Gag Processing at the Plasma Membrane through Gag-Pol Dimerization

Abstract: d Efavirenz (EFV), a nonnucleoside reverse transcriptase (RT) inhibitor, also inhibits HIV-1 particle release through enhanced Gag/Gag-Pol processing by protease (PR). To better understand the mechanisms of the EFV-mediated enhancement of Gag processing, we examined the intracellular localization of Gag/Gag-Pol processing products and their precursors. Confocal microscopy revealed that in the presence of EFV, the N-terminal p17 matrix (p17MA) fragment was uniformly distributed at the plasma membrane (PM) but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 69 publications
(83 reference statements)
4
25
0
Order By: Relevance
“…Collectively, these data reveal that the NNRTIs EFV and RPV significantly attenuate the kick of latent HIV-1 from resting CD4 ϩ T cells by inhibiting the release of HIV-1 virus particles. This finding is consistent with our prior work, which demonstrated that potent NNRTIs impact the late stages of HIV-1 replication (13), leading to a decrease in virus production from HIV-1-transfected 293T or HeLa cells (14,15). Specifically, NNRTIs enhance Gag-Pol polyprotein precursor dimerization, likely after plasma membrane targeting but before complete particle assembly, resulting in uniform distribution of p17 matrix to and dissociation of p24 capsid and reverse transcriptase from the plasma membrane (13)(14)(15).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Collectively, these data reveal that the NNRTIs EFV and RPV significantly attenuate the kick of latent HIV-1 from resting CD4 ϩ T cells by inhibiting the release of HIV-1 virus particles. This finding is consistent with our prior work, which demonstrated that potent NNRTIs impact the late stages of HIV-1 replication (13), leading to a decrease in virus production from HIV-1-transfected 293T or HeLa cells (14,15). Specifically, NNRTIs enhance Gag-Pol polyprotein precursor dimerization, likely after plasma membrane targeting but before complete particle assembly, resulting in uniform distribution of p17 matrix to and dissociation of p24 capsid and reverse transcriptase from the plasma membrane (13)(14)(15).…”
supporting
confidence: 93%
“…This finding is consistent with our prior work, which demonstrated that potent NNRTIs impact the late stages of HIV-1 replication (13), leading to a decrease in virus production from HIV-1-transfected 293T or HeLa cells (14,15). Specifically, NNRTIs enhance Gag-Pol polyprotein precursor dimerization, likely after plasma membrane targeting but before complete particle assembly, resulting in uniform distribution of p17 matrix to and dissociation of p24 capsid and reverse transcriptase from the plasma membrane (13)(14)(15). Interestingly, in the HeLa and 293T cells, micromolar concentrations of EFV were required to see a significant reduction in virus production (14,15).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with the studies summarized in this review, indicating that processing of the p51-RH bond is dependent on RH unfolding, which in turn depends on dimer formation. Experimental studies supporting the cooperativity of dimer formation have been reported by Figueiredo et al [87] and Sudo et al [117], who showed that the addition of EFV or other dimer-inducing NNRTIs to HIV-transfected cells led to premature PR activation, resulting in intracellular processing of the polyprotein and a decrease in viral particle production. In this case, the order of dimer formation differs from that illustrated in Figure 16.…”
Section: Maturation Within the Virionmentioning
confidence: 72%
“…This type of arrangement also shields potential cleavage sites in the folded domains from HIV protease and form proteases present in the host cell. Dimerization of the polyprotein is facilitated by anchoring of the myristoylated polyprotein in the membrane [116,117], and becomes more probable at the higher concentrations present in the virion—initial concentrations of Gag and Gag-pro-Pol are estimated as 3.6 mM and 0.2 mM, respectively [118], facilitating the formation of the active HIV protease dimer necessary for viral maturation.…”
Section: Maturation Within the Virionmentioning
confidence: 99%